2017
DOI: 10.12681/bgsg.11199
|View full text |Cite
|
Sign up to set email alerts
|

The Greek Catalogue of Active Faults and Database of Seismogenic Sources

Abstract: The new reasearch project to create the Greek Catalogue of Active Faults and Database of Seismogenic Sources has three major goals: (i) the systematic collection of all available information concerning neotectonic, active and capable faults as well as broader seismogenic volumes within the Aegean Region; the search will be mainly based on geological and geophysical data; (ii) the quantification of the principal seismotectonic parameters of the different sources and the associated degree of uncertainty; (iii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…was presented by Pavlides et al, (2008) and Pavlides et al, (2010), focused on the North Aegean region and by Caputo et al, (2012) and Sboras (2012) on northern Greece.…”
Section: XLVII No 2 -518mentioning
confidence: 88%
“…was presented by Pavlides et al, (2008) and Pavlides et al, (2010), focused on the North Aegean region and by Caputo et al, (2012) and Sboras (2012) on northern Greece.…”
Section: XLVII No 2 -518mentioning
confidence: 88%
“…The recent evolution of the northern Aegean is characterized by the westward motion of the Anatolian plate along the North Anatolian Fault (e.g. Jolivet, 2011) which in turn pushes the Aegean plate southwards (Papazachos, Kiratzi, & Kontopoulou, 1998;Pavlides et al, 2010). The main active tectonic structures in the study area can be found in the Greek Database of Seismogenic Sources -GreDaSS which done by a group of researchers (Caputo, Chatzipetros, Pavlides, & Sboras, 2013).…”
Section: The Northern Aegean Seismic Activity and The Strong Earthquamentioning
confidence: 99%
“…It was only until recently when such databases started to be developed for the Aegean region. "GreDaSS" (Greek Database of Seismogenic Sources; Pavlides et al 2010;Sboras 2011;Caputo et al 2012) is an updatable openfile GIS-based database of the seismic sources in the broader Aegean region that uses multi-layer fault/source modelling according to the needs of the end-user. Since the prime purpose of GreDaSS is seismic hazard assessment, the fault/source models are geometrically simplified, but fully parameterized with explicitly defined seismotectonic parameters.…”
Section: The Seismic Sources Dataset/layermentioning
confidence: 99%